Chlamydophila psittaci and Toxoplasma gondii infection in pigeons (Columba livia) from São Paulo State, Brazil - de Lima, Vanessa Yuri [UNESP]; Langoni, Hélio [UNESP]; da Silva, Aristeu Vieira; Pezerico, Sandia Bergamaschi [UNESP]; Barbosa de Castro, Andre Peres; da Silva, Rodrigo Costa [UNESP]; Araújo Junior, João Pessoa [UNESP] (Elsevier B.V., 2011)
Pigeons (Columba livia) cohabit with humans in urban and rural areas, representing a public health problem since microorganisms are transmitted through the inhalation of dust from their dry feces (chlamydiosis) and through ingestion of their undercooked or poorly refrigerated meat (toxoplasmosis). This study aimed to evaluate the presence of Chlamydophila psittaci and Toxoplasma gondii in pigeons from four cities in São Paulo State, Brazil. C psittaci was evaluated through hemi-nested polymerase chain reaction (hnPCR) using cloacal and tracheal swabs, whereas T. gondii specific antibodies were assessed by means of modified agglutination test (MAT), mouse brain and muscle bioassay, and polymerase chain reaction (PCR). To confirm the infection in mice, T. gondii antibodies were assayed by using indirect fluorescent antibody test (IFAT). Considering C. psittaci, 40/238 (16.8%; 95%CI 12.6-22.1%) samples were positive according to hnPCR, especially for the cities of São Paulo (42.5%) and Bauru (35%). As regards T. gondii, 12/238 (5%; 95%CI 2.9-8.6%) serum samples were positive according to MAT. of these, five samples had titer equal to 1:8; six samples, 1:16; and one sample, 1:32. Bioassay, IFAT and PCR were negative for mouse toxoplasmosis. The absence of T. gondii antibodies suggests that pigeons may be infected with a low concentration of the agent, not detected by the antigen test. Thus, C. psittaci represents an actual problem concerning bird health. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Columba livia; Chlamydophila psittaci; Toxoplasma gondii; Zoonosis; Infection source; Diagnosis